Kepentingan Tiongkok Dalam Akuisisi Pelabuhan Hambantota Sri Lanka - Permana Putera, I Gst Ngr Arya; Fasisaka, Idin; Intan Prameswari, Anak Agung Ayu (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2019)
ABSTRACT Hambantota Port is a Sri Lankan port built through Chinese receivables. After seven years of operation, in 2017 the port was officially acquired by China. Although constrained by rules that forbid China’s acquisition and bad port’s performance, the acquisition is still carried out through the exchange of Chinese receivables. This study aims to explain the interests of China in the acquisition of Hambantota Port with research limitations between 2010-2017. The research method used is a descriptive study case with a qualitative approach, and the technique of data collection use library research and through online data research. This research will be analyzed through the geopolitical perspective, focus on Place concept and Debt-Equity Swap concept. The exchange of receivables is not always made creditor country loss. Focusing on the place of Hambantota Port, the acquisition can help China realize the Maritime Silk Road initiative, secure the route of China’s energy needs, and increase Chinese influence in the Indian Ocean Region. Keywords: China, Hambantota Port, Port Acquisition